2022
DOI: 10.3934/microbiol.2022015
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and development of high-resolution melting curve analysis (HRMA) assay for detection of New Delhi metallo-β-lactamase (NDM) producing <i>Pseudomonas aeruginosa</i>

Abstract: <abstract> <p>New Delhi metallo-β-lactamase-1 (NDM-1) producing <italic>Pseudomonas aeruginosa</italic> strain detection plays a vital role in confirming bacterial disease diagnosis and following the source of an outbreak for public health. However, the standard method for NDM-1 determination, which relies on the features of the colony of the bacteria cultured from the patient's specimen, is time-consuming and lacks accuracy and sensitivity. This study aimed to standardize a high-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…DNA template, primers and annealing temperature were important for accurate HRM curve profiling [26,27]. Most studies recommended higher annealing temperature for melting curve profiling [26][27][28]. Our optimization of SSR-HRM indicated that a low annealing temperature (56 • C, Groups 1, 4, 7) resulted in nonspecific amplification which generated incorrect SSR genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…DNA template, primers and annealing temperature were important for accurate HRM curve profiling [26,27]. Most studies recommended higher annealing temperature for melting curve profiling [26][27][28]. Our optimization of SSR-HRM indicated that a low annealing temperature (56 • C, Groups 1, 4, 7) resulted in nonspecific amplification which generated incorrect SSR genotyping.…”
Section: Discussionmentioning
confidence: 99%